Pelatihan Penggunaan Microsoft Forms Dalam Pembelajaran Online - Subandi, Subandi; Wiharto, Yudi; Mufti, Mufti; Gata, Grace; Aryasanti, Agnes; Saputro, Ari (Journal Of Computer Science Contributions (JUCOSCO), 2023)
SMPN 18 Tangerang Selatan has adopted online learning as a response to the COVID-19 pandemic situation.However, there are still challenges in optimizing the online learning experience. For this reason, training on theuse of Microsoft Forms was carried out to provide understanding and skills to teachers in using this tool toincrease interactivity and data collection in the online learning process. This training aims to provideunderstanding and skills to SMPN 18 Tangerang Selatan teachers in using Microsoft Forms in online learning.Teachers are expected to utilize this tool to create interactive quizzes, surveys, and forms that can be used in datacollection and student evaluation. Training method with socialization and introduction, the training begins withan outreach session about the purpose of the training, the benefits of using Microsoft Forms, and examples of usein the context of online learning, followed by step-by-step demonstrations, practical exercises and discussions.The results of this training had a positive impact on the knowledge and skills of the participants as seen from theresults of the training evaluation which achieved a 94% level of understanding in using Microsoft Forms. Theconclusion of this training activity, by paying attention to the needs of teachers and providing appropriate trainingmethods, this training is very effective in increasing teachers' ability to use Microsoft Forms in the context ofonline learning.